DESA DIGITAL: PELUANG UNTUK MENGOPTIMALKAN PENYEBARLUASAN PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Wijaya, Endra; Anggraeni, Ricca; Bachri, Rifkiyati (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Law can be one medium to achieve social welfare. As soon as the law is formed, including the one in the form of legislation, it must be disseminated. The dissemination according to Regulations Number 12 Year 2011 about the Formation of Legislation is performed by the Government in the state gazette of the Republic of Indonesia or the News of the Republic of Indonesia through the electronic or printed media so that the community will find out and understand the content and intent of the legislation. Ideally, the dissemination of legislation is performed evenly to all of the society, starting from the central level to the regions and even to the rural area. Digital village program, connected with the internet access, is a good opportunity which can be empowered to optimize the dissemination of legislation up to the rural area. Key words : promulgation of law, use of internet, digital village